2021
DOI: 10.1016/j.esmoop.2021.100318
|View full text |Cite
|
Sign up to set email alerts
|

Sequential first-line treatment with nab-paclitaxel/gemcitabine and FOLFIRINOX in metastatic pancreatic adenocarcinoma: GABRINOX phase Ib-II controlled clinical trial

Abstract: Background: Nab-paclitaxel/gemcitabine (AG) and FOLFIRINOX (FFX) are promising drugs in metastatic pancreatic cancer (MPC). This study evaluated a new first-line sequential treatment (AG followed by FFX) in MPC that might overcome resistance to primary therapy and delay tumor progression. Patients and methods: Patients with histologically/cytologically confirmed MPC were included in a multicentric trial receiving AG (day 1, 8 and 15) followed by FFX (day 29 and 43). In phase Ib, three dose-levels were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Three included studies, encompassing 144 patients, reported on the prevalence of VTE in pancreatic cancer patients [ 32 , 33 , 81 ]. However, a meta-analysis could not be performed due to insufficient number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three included studies, encompassing 144 patients, reported on the prevalence of VTE in pancreatic cancer patients [ 32 , 33 , 81 ]. However, a meta-analysis could not be performed due to insufficient number of studies.…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot showing the estimated overall pooled prevalence of VTE in cancer patients undergoing chemotherapy [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , …”
Section: Figurementioning
confidence: 99%
“…Therefore, 5-FU and PTX, which are critical in the clinic in the present study, were selected. The 5-FU inhibits the DNA synthesis by reducing thymidylate synthase activity, while PTX inhibits depolymerization of tubulin and subsequent cell division ( 21 , 22 ). Dysregulation of various components in distinct pathways is the major common cause for drug resistance, including alterations in drug transport, EMT transition, miRNA dysregulations, cell cycle changes, autophagy regulation, DNA damage repair machinery, tumor microenvironment interactions, and stemness enhancement ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“… 22 New regimens such as FOLFIRINOX and AG have shown stronger effects in pancreatic cancer patients. 23 Yet the single use of gemcitabine and combined regimens containing gemcitabine are still applied in quite a high proportion of advanced pancreatic cancer patients. 24 , 25 Patients that accept gemcitabine-based chemotherapy as first-line therapy usually receive single drug or combined regimens containing 5-FU, capecitabine or S-1 after disease progression.…”
Section: Discussionmentioning
confidence: 99%